Answer is 1.5
You would first find the mean, you add all together then divided it by the numbers that it has, they have 4 number -3, -2, -1, 2 in this problem.
Add all number together divided it by 4, you'll get -1, (-3 + -2 + -1 + 2) ÷ 4 = -1) Then you subtract the mean by the numbers you used to get your mean so in this case it is 3, -2, -1, 2.
-3-(-1)= -2
-2-(-1)= -1
-1-(-1)= 0
2-(-1)= 3
Then you add the answers up but you have to turn the negative numbers to positive like -2 turns into just 2 and so does -1 to 1. (2+1+0+3= 1.5) Then you divide the 6 by how many numbers there are so in this case there are 4 numbers so you do 6 divided by 4 and you get 1.5. (Trust me I learned this)